2018
DOI: 10.4038/ss.v48i1.4710
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Validity of Conditional Four Moment Capital Asset Pricing Model: Empirical Evidence from the Colombo Stock Exchange

Abstract: The Capital Asset Pricing Model (CAPM) is one of the most used model in finance during the last five decades. This is despite heavy criticism against it along with an ongoing debate among academia about the empirical validity of the model. Three major extensions to the conventional model have been suggested; higher-moment CAPM, multi-factor model and conditional CAPM. All these models have shown mixed results in empirical studies. In the recent past, these extensions are integrated and tested for empirical val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(130 reference statements)
0
0
0
Order By: Relevance
“…Vendrame et al [8] showed that investors forego some returns (for the same variance) for positive skewness while for positive cokurtosis, the investors need to be compensated as it delivers large losses for expecting higher expected returns. Nishantha [25] showed that coskewness was found to be significant while the covariance and cokurtosis were insignificant in explaining the returns of stocks in Colombo Stock Exchange. This article incorporates conditional co-skewness and co-kurtosis into the traditional CAPM model by Sharpe-Lintner, aiming to analyze the impact of conditional higher moments on the returns of sectoral indices listed in the BSE within the Indian context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vendrame et al [8] showed that investors forego some returns (for the same variance) for positive skewness while for positive cokurtosis, the investors need to be compensated as it delivers large losses for expecting higher expected returns. Nishantha [25] showed that coskewness was found to be significant while the covariance and cokurtosis were insignificant in explaining the returns of stocks in Colombo Stock Exchange. This article incorporates conditional co-skewness and co-kurtosis into the traditional CAPM model by Sharpe-Lintner, aiming to analyze the impact of conditional higher moments on the returns of sectoral indices listed in the BSE within the Indian context.…”
Section: Literature Reviewmentioning
confidence: 99%